Stylet slow-pull vs. standard suction technique for endoscopic ultrasound-guided fine needle biopsy in pancreatic solid lesions using 20 Gauge Procore™ needle: A multicenter randomized trial. Issue 2 (February 2020) - Di Mitri, Roberto; Mocciaro, Filippo; Antonini, Filippo; Scimeca, Daniela; Conte, Elisabetta; Bonaccorso, Ambra; Scibetta, Nunzia; Unti, Elettra; Fornelli, Adele; Giorgini, Sara; Binda, Cecilia; Macarri, Giampiero; et al.
Abstract: Background: Standard suction and slow-pull techniques have been utilized during endoscopic ultrasound-guided fine needle aspiration of pancreatic solid lesions, but the correct sampling technique remains unclear. New needles designed to obtain samples suitable for histological evaluation have become available. We performed a study comparing the two sampling methods during endoscopic ultrasound-guided fine needle biopsy (EUS-FNB) in patients with pancreatic solid lesions. Methods: We performed EUS-FNB with a 20 Gauge FNB needle using slow-pull or standard suction techniques in a prospective, randomized, multicenter study. The primary aim was bloodiness of the collected specimens. Secondary aims were technical success and performance of the two techniques. Results: 110 patients were included (55 per group). No difference in blood contamination was observed (slow-pull 80% vs. suction 74%, p = 0.917). Technical success was 95% (96% vs. 94%, p = 0315). Sensitivity (96% vs. 93%), specificity (100% vs. 100%), positive likelihood ratio (NA), negative likelihood ratio (0.04 vs. 0.07), diagnostic accuracy (96 vs. 93%) did not differ between the two groups. Conclusion: EUS-FNB with slow-pull and standard suction techniques are comparable in terms of blood contamination providing similar high diagnostic sensitivity and accuracy in pancreatic solid lesions. The use of the new generation FNB needle allows to reach such high level of diagnostic adequacy regardless of the technique utilized.